Removal of Chromium(VI) from Aqueous Solutions Using Activated Carbon Prepared From Flame Tree Seed Coat - STANLY, S.; SELVAKUMAR, S.; ARABINDOO, BANUMATHI (Asian Journal of Chemistry, 2010)
A new low cost activated carbon prepared from flame tree seed coat (FTSC) by acid process followed by thermal activation was used as an adsorbent in the present investigation for the removal of chromium(VI) from its aqueous solution. The efficiency of the activated carbon in the removal of chromium(VI) was studied under various experimental conditions such as dosage of adsorbent, pH and contact time. More than 85 % removal was achieved under optimal conditions. The adsorption obeys Freundlich adsorption isotherm.